2019
DOI: 10.1021/acsinfecdis.8b00370
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of Murine Cutaneous Lesions Induced by Leishmania amazonensis or Leishmania major

Abstract: Cutaneous leishmaniasisis is the most common clinical form of leishmaniasis and one of the most relevant neglected diseases. It is known that the progress of the disease is species specific and the host's immune response plays an important role in its outcome. However, the pathways that lead to parasite clearance or survival remain unknown. In this work, skin tissue from mice experimentally infected with L. amazonensis, one of the causative agents of cutaneous leishmaniasis in the Amazon region, L. major, anot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Despite the different experimental conditions and setup, heat-shock and Tryparedoxin related proteins were differentially regulated in 17 studies, indicating that those proteins are often modulated in the parasite. Moreover, several proteins were consistently identifiable and also to be similarly modulating in studies with similar experimental conditions [ 42 , 40 , 41 ]. Only three studies explored the host response (human subjects) during Leishmania infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the different experimental conditions and setup, heat-shock and Tryparedoxin related proteins were differentially regulated in 17 studies, indicating that those proteins are often modulated in the parasite. Moreover, several proteins were consistently identifiable and also to be similarly modulating in studies with similar experimental conditions [ 42 , 40 , 41 ]. Only three studies explored the host response (human subjects) during Leishmania infection.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the study reported U6 snRNA-associated Sm-like protein and heat repeat-containing protein 3 to be precisely up-regulated in infection with L. major , while protein tweety homolog 3, phosphatidate cytidylyltransferase, and macrophage metalloelastase to be precisely up-regulated in infection with L. amazonensis . Overall, the studies by Negrão et al [ 40 , 42 , 41 ] demonstrated the species-specific protein modulation in Leishmania infection as well as differentiated the host response through LPS inoculation and Leishmania infection. To observe the immune response effects of malnutrition in Leishmania infection, Losada-Barragán et al [ 43 , 44 ] conducted the differential proteomic studies involving malnourished mice.…”
Section: Differentially Modulated Proteins In the Host After mentioning
confidence: 99%
See 2 more Smart Citations
“…Proteomic MS has enabled detection of changes in the host protein expression profiles in macrophage in vitro infection models [15,16], murine and human cutaneous lesions [17,18] and in the serum of infected individuals [19]. Proteomic MS studies have demonstrated that the Leishmania infection causes a species-specific reprogramming of major metabolic pathways in the host cell [16].…”
Section: Characterizing Leishmania-host Interactionsmentioning
confidence: 99%